2013
DOI: 10.4238/2013.may.13.1
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide analysis of the ERF gene family in sorghum

Abstract: ABSTRACT. The ethylene response factor (ERF) family are members of the APETALA2 (AP2)/ERF transcription factor superfamily; they are known to play an important role in plant adaptation to biotic and abiotic stress. ERF genes have been studied in Arabidopsis, rice, grape, and maize; however, there are few reports of ERF genes in sorghum. We identified 105 sorghum ERF (SbERF) genes, which were categorized into 12 groups (A-1 to A-6 and B-1 to B-6) based on their sequence similarity, and this new method of classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 46 publications
(50 reference statements)
1
46
0
Order By: Relevance
“…9). We found that Z. mays has 105 ERF genes which are greater than Arabidopsis, sorghum, peach and moso bamboo, while less than Chines cabbage and Carrot ( In chromosomal maps, distribution of ZmERF genes in all the 10 chromosomes was similar to the findings of AP2/ERF in Sorghum (Yan et al, 2013) and Chinese cabbage (Song et al, 2013). Interestingly, ERF gene comprising of same group and present on same chromosome forming cluster, was also observed in Arabidopsis (Sakuma et al It has been found that intron/exon position configuration provides hint in evolutionary relationship (Hu and Liu, 2011).…”
Section: Gene Ontology Annotationsupporting
confidence: 63%
See 2 more Smart Citations
“…9). We found that Z. mays has 105 ERF genes which are greater than Arabidopsis, sorghum, peach and moso bamboo, while less than Chines cabbage and Carrot ( In chromosomal maps, distribution of ZmERF genes in all the 10 chromosomes was similar to the findings of AP2/ERF in Sorghum (Yan et al, 2013) and Chinese cabbage (Song et al, 2013). Interestingly, ERF gene comprising of same group and present on same chromosome forming cluster, was also observed in Arabidopsis (Sakuma et al It has been found that intron/exon position configuration provides hint in evolutionary relationship (Hu and Liu, 2011).…”
Section: Gene Ontology Annotationsupporting
confidence: 63%
“…AP2 binds to GCAC(A/G)N(A/T)TCCC(A/G)ANG(C/T) (Gong et al, 2008;Wilson and Krizek, 2000). The ERF-associated amphiphilic repression (EAR) motif was also identified in many species of plant like Arabidopsis, Z. mays and sorghum (Yan et al, 2013). The three dimensional analysis of AP2/ERF protein domain shows it consist of 3 anti-parallel beta-sheet and one alpha-helix (Yamasaki et al, 2013) arginine and tryptophan in beta-sheet have basic function in formation of GCC box binding domain and serine/threonine also important residue for DNA binding domain (Shanker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AP2/ERF TF families have been identified and characterized in dicotyledonous and monocotyledonous plants (Sakuma et al 2002;Nakano et al 2006;GilHumanes et al 2009;Yan et al 2013;Sun et al 2014). Homologs of the AP2-containing proteins have also been found in gymnosperms, bryophytas, and chlorophytes (Shigyo et al 2006), with even similar sequences in bacteria and viruses (Magnani et al 2004;Balaji et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that there are 122, 139, and 105 ERF members in Arabidopsis, rice, and sorghum, respectively (Nakano et al, 2006, Yan et al, 2013. It is likely that only a small group of the ERFs are related to ethylene responses.…”
Section: Erfsmentioning
confidence: 97%